2011
DOI: 10.5090/kjtcs.2011.44.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Duct Cyst in Mediastinum - A case report -

Abstract: The thoracic duct cyst is an extremely rare cystic lesion in the mediastinum. Surgical treatment of the cyst is necessary to confirm histologic diagnosis and prevent potential complications such as spontaneous or traumatic rupture of the cyst and chylothorax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Resection is often recommended to confirm histology and to prevent spontaneous rupture and subsequent chylothorax. [ 4 ] TDCs are also removed for symptomatic relief and to reduce the theoretical risk of potential malignant transformation, although there have not yet been any published cases that describe malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Resection is often recommended to confirm histology and to prevent spontaneous rupture and subsequent chylothorax. [ 4 ] TDCs are also removed for symptomatic relief and to reduce the theoretical risk of potential malignant transformation, although there have not yet been any published cases that describe malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…In magnetic resonance imaging, signals indicating a high concentration of lipids in the cyst can aid in the diagnosis. Fine-needle aspiration is another option; however, the diagnosis should then be pathologically confirmed after surgical resection [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, thoracic duct cysts are treated using surgical resection [ 6 ]. Although some reports have argued that surgical resection is unnecessary, surgical resection of thoracic duct cysts should be performed to avoid chylothorax if the cyst ruptures into the pleural cavity [ 6 ]. Chylothorax is the most common postoperative complication, making ligation of all branches of the thoracic duct mandatory [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kwak and Bae [6] reported that they ligated the thoracic duct and that the chylothorax was not observed thereafter. In the case of a mediastinal cystic mass that is adjacent to the esophagus, the mass may originate from the thoracic duct.…”
Section: Discussionmentioning
confidence: 99%